Prospek Pusat Informasi dan Perpustakaan dalam Perkembangan Information And Communication Technology (ICT) : Tinjauan Komprehensif Nilai Filosofi Ilmu Informasi dan Perpustakaan - Iswanto, Rahmat; Sulistyowati, Sulistyowati (TIK ILMEU : Jurnal Ilmu Perpustakaan dan Informasi, 2018)
This article is intended to see the future existence of the institution of information center and library as an institution that will continue to exist even if the information could be found by the community easily through the development of information and communication technology. In the present, people can access information through any approach in the worlds information network known as the internet. Moreover, if in the future the ability of people to choose the type of information needed better. Therefore it becomes a matter as how the prospect of information center and library in the development of Information and Communication Technology (ICT). By exploring the Information Science and Library as a fundamental branch of science, both seen from ontology, epistemology, and axiology is expected to know the basics of the prospects of information centers and libraries. The things that the information center and library should do will be seen through this assessment so that it will provide very useful inputs.